Ibn Khaldun’s Theories of Perception, Logic and Knowledge: An Islamic Phenomenology (American Journal of Islam and Society, 1985)
Ibn Khaldun’s theories about perception, logic and knowledge are clearlyinfluenced by Aristotelian thought; however being somewhat ecclectic, he adds,synthesizes and arrives at his own perspective. In addition, however novelIbn Khaldin’s conclusions may be, there is the underlying awareness of theSource of all knowledge: “Knowledge comes only from Allah, the Strong,the Wise.” His philosophy, guided by the Qur’an and the Sunnah and sparkedby his own genius and capacity for speculative thought, sometimes has muchin common with Scholastic Realism, and indeed might be classified as IslamicPhenomenology.According to Ibn Khaldun, man is set apart from the lower stages of Allah’screations by his ability to think. Through this ability and the existence of thesoul, he is able to move towards the world of the angels, the essence of whichis pure perception and absolute intellection. It is the world of the angels whichgives the soul power of perception and motion. Just as the stages are connectedupward, so they are connected downward. For example, the soul acquiressense perceptions from the body as preparation for actual intellectionand acquires supernatural perceptions from the angel stage for knowledge ofa timeless quality. Some scholars have attributed Ibn Khaldun’s descriptionof spheres of existence to Rasa’il Ikhwan As-Safa’ as he was most probablyexposed to them via the school of Abu Al-Qasim Maslamah Al-Majriti inCordova. But , the seventh epistle of the Rasa’il, which deals in detail withthe spheres of existence, does not contain Ibn Khaldtin’s concept of upwardand downward movement, rather it describes a Platonic view of the soul ...